Synthesis, characterization and evaluation of palm oil-based polyurethane scaffolds as candidate biomaterial / Ng Wei Seng - Ng , Wei Seng (2018)
Biodegradable water-blown porous polyurethane scaffolds were synthesized by reacting a blend of commercial polyols and the newly synthesized palm oil-based polyester polyol (PPP) with aliphatic isophorone diisocyanate (IPDI) by one-shot foaming method at room temperature. PPP was prepared from deacidified glycerol monostearate (DGMS) and glutaric acid via direct polycondensation reaction. The effect of modification of polyurethane system with increasing content of PPP on the physico-chemical, mechanical, thermal and biodegradation properties of polyurethane scaffolds were investigated. The resulting polyurethane scaffolds were characterized by Attenuated Total Reflectance - Fourier Transform Infrared (ATR-FTIR), Instron Universal Testing Machine, Simultaneous Thermal Analyzer (STA), Differential Scanning Calorimeter (DSC) and Scanning Electron Microscope (SEM). The modification of polyurethane with PPP improved pore size and cell compactness, tensile strength, Young’s modulus and elongation at break of the polyurethane scaffolds. In terms of biodegradation properties, all the modified polyurethane scaffolds were susceptible to hydrolytic and enzymatic degradation. The degradation of modified polyurethane scaffolds did not incur significant changes in pH of the medium used. After 7 days of enzymatic degradation, polyurethane scaffolds prepared with 100 wt. % and 75 wt. % of PPP maintained 90% and 70% of the tensile strength, respectively. The cytotoxicity studies on polyurethane scaffolds were evaluated employing mouse fibroblast 3T3 and human osteosarcoma MG63 cells, qualitatively and quantitatively. Polyurethane incorporated with PPP resulted in increase of biocompatibility. Polyurethane scaffold, P100 exhibited good biocompatibility and better adhesion with 3T3 and MG63 cells. The materials however presented moderate toxic effect on MTT assay after 7 days of incubation. The current work demonstrated that the modification of water-blown porous polyurethane formulation with PPP allow improvement in physical and mechanical properties as well as tunable degradation rate with sustained mechanical strength, which may suitably use in soft tissue engineering applications.